Raise your hand [videorecording (DVD)] - Rae, Jessica; Dancy, Chanda, 1978-; Corchado, Jearnest; Taylor, Hanani; Steingold, Joel; Nurse, Jess (Freestyle Digital Media, 2025)
Gia and her best friend, Lila, try to survive a rough neighborhood where every kid has a sad story to tell.